Therapeutic targeting of alternative splicing - Jarosław Paluszczak (Polish Pharmaceutical Society, 2019)
Gene transcription leads to the generation of pre-mRNA molecules which contain both coding sequences (exons) and intervening non-coding sequences (introns). The primary transcript needs further processing which involves the excision of introns and ligation of exons. This process is called RNA splicing. Nearly all primary transcripts undergo alternative forms of splicing, which may lead to exon skipping or intron inclusion in the final mRNA. Thus, the translation of alternatively spliced RNA molecules results in the formation of slightly different proteins, which may, in some cases, exert antagonistic activity. Splicing is a multistage process which is conducted by a complex machinery comprising small nuclear RNA molecules and many proteins called splicing factors. The process undergoes precise regulation by means of cis acting internal RNA sequences and trans acting protein factors which may either enhance or silence the splicing of an exon. Many diseases are associated with aberrations of alternative splicing and its modulation may be used therapeutically, e.g. for the treatment of spinal muscular atrophy (SMA) or Duchenne muscular dystrophy (DMD). This article presents current knowledge of the ways of pharmacological modulation of alternative splicing. The focus is on the use of those therapeutics which have been already approved for clinical application or have entered clinical trials. The chemistry and mechanism of action of specific splice switching oligonucleotides is presented. Nusinersen promotes exon inclusion during splicing of SMN2 and is used for SMA treatment. On the other hand, eteplirsen is an oligonucleotide promoting exon skipping during splicing of mutated DMD and has been conditionally approved for DMD treatment. Moreover, small molecule modulators of alternative splicing (e.g. branaplam) are also described. The dynamic developments in this field should result in the approval of new drugs acting by the modulation of alternative splicing in the nearest future.